2 - The Rise of Open Access Journals: Their Viability and Prospects for the African Scholarly Community - Allison Möller (Africa Media Review, 2007)
Electronic publishing has enabled the publisher of scholarly journals to offer an enhanced high quality product, but one that comes bundled with unsatisfactory conditions: high prices, inflexible terms and copyright obstacles that severely restrict the optimal flow and use of information. Dissatisfied with the terms and limitations of traditional journals, individuals, groups and organisations have opted to advance a different model of journal. The open access movement may be seen as part of a critical trend that seeks to break the stranglehold of commercial expropriation of information. Open access journals are freely available for reading, copying, and disseminating. With growing support from many different quarters, the challenger to the 3.5 billion publishing industry packs a potentially destabilising punch. This paper will cover the rise of open access journals and examine the economics of the ‘author pays’ business model. Notwith-standing the appreciable benefits to readers, the impetus to overturn deeply entrenched traditions must also overcome significant barriers. These include the practice of the academic reward system, funding issues, perceptions about quality and integrity, as well as the fundamental problem of the digital divide. While the open access model also presents a serious threat to scholarly society publications, all initiatives to promote visibility of African journals should be explored.